The local network. Preliminary remarks on distribution and trade of coarse ware in Northern Italy - Ardis, Carla; Riccato, Anna (Rei Cretariae Romanae Fautorum Acta, 2023)
This research aims to reconstruct the pattern of distribution of coarse ware in Northern Italy in the Roman period and to identify preferential trade routes within the network of inland waterways and terrestrial roads. A peculiar vessel has been selected as a case study; its distinctive feature is its prominent shoulder, sharply separated from the neck and usually simply decorated. Through a comprehensive survey of the published literature, the present paper shows that these vessels were spread throughout the whole of Northern Italy. The River Po was the preferred route for the diffusion of these vases, whose trade flowed from west to east. Interestingly enough, the W-E direction of this trade network was reconstructed using materials from Aquileia, which is the arrival point. The originality of the present work lies in its focus on coarse ware that testifies to regional exchanges, bringing to light the role Aquileia played in connecting the Regio X and the neighbouring areas.